The Influence of Experiential Marketing, E-Service Quality (WebBased Tracking System) And Trust On Customer Satisfaction In J&T Express Service Users In Kab. Pasuruan - Miftahul Huda; Fitri Anisa (Fakultas Bisnis, 2020)
The role of a shipping service company is very important to the development of the society and lifestyle of today, the role as a media distribution of goods. With the delivery service is very easy for consumers to fulfill their needs, but it can save time and also make consumers feel happy things can be done easily. The purpose of this research is to know the influence of Experiential Marketing, E-Service Quality (Web based Tracking System) and trust in customer satisfaction in service users J&T Express in Pasuruan whose results can be used as an evaluation of J&T Express to improve its performance. The population in this research is a customer who has been delivering goods at J&T Express in Pasuruan. The number of samples in this study used Machin formula and was found to be 132 respondents or a service user of J&T Express in Pasuruan. The results of this study show that Experiential Marketing, E-Service Quality and trust have a positive and significant effect on customer satisfaction, so that J&T Express is expected to develop and as well as maintain Experiential Marketing, EService Quality and customer confidence so that later to increase customer satisfaction.